Persistent left superior vena cava frequency in congenital heart surgery and its effect on surgical strategy (Annals of Medical Research, 2022)
Aim: Persistent left superior vena cava encompasses a wide range of systemic venous anomalies. Persistent left superior vena cava is relatively infrequent and, under normal circumstances, asymptomatic but may be of clinical importance in cardiac surgery. This study aims to investigate the effect of persistent left superior vena cava on surgical planning.Material and Methods: We included a total of 525 consecutive patients (310 males, 215 females) who underwent open-heart surgery for congenital heart disease. The association of persistent left superior vena cava with congenital anomalies and surgical approaches were recorded. Demographic data and outcome data were retrospectively analyzed.Results: Persistent left superior vena cava was observed in 28 (5.3%) patients. The drainage point of PLSVC was coronary sinus in 23 (82.1%) patients, left atrium in 5 (17.9%) patients. The mean age and weight of the patients were 11.5 months (range, one day to 18 years), 9.3 kg (range, 0.5-65 kg), respectively. Persistent left superior vena cava was obtained in 11 (39.4%) patients with echocardiography, 12 (%42.8) patients with cardiac catheterization and tomography imaging, and 5 (17.8%) patients during surgery. Surgical management of the PLSVC included of temporary occlusion in 17 (60.7%) patients, direct cannulation in 6 (21.5%) patients, Glenn shunt in 2 (7.1%) patients, intracardiac rerouting in 2 (7.1%) patients and ligation in 1 (3.6%) patient. No operative morbidity and complication associated with persistent left superior vena cava were seen.Conclusions: Consequently, persistent left superior vena cava is relatively infrequent, but the surgical team should be aware of this anomaly, its draining points, and possible complications, and it must be kept in mind simple and effective solutions about persistentleft superior vena cava.
Keywords: Coronary sinus; left atrium; persistent left superior vena cava; surgery